Reducing Radicalism as a Form of Intervention Through the Role of School and Education Curriculum - Rahmanto, Didik Novi; Meliala, Adrianus E.; Lolo, Ferdinand Andi (JPI (Jurnal Pendidikan Indonesia), 2020)
Â Radicalism become a severe problem for the peace and security of society in Indonesia. So it is necessary to optimize the role of educational institutions in preventing and offering alternative solutions to the movement of negative radicalism through dialogue and education in schools, from elementary to higher education level.This study aims to examine the role of school and aducation curriculum as an effort in reducing radicalism. This research is a qualitative study which uses in-depth interviews and literature studies in gathering data. The analysis was carried by using the age graded theory of crime. The results shows that school and education curriculum have a role in reducing radikalism. School is a social institution that is very important in each phase of individual growth because schools have a huge role in carrying out positive social values. Therefore, the education curriculum can be arranged in reducing radicalism in society by increasing the portion of cultural values, humanity, tolerance, and the attachment of individuals to their environment.